Manajemen Kelas dalam Pembelajaran Matematika Kelas Unggulan di MTs Nurul Huda NU Pesanggrahan Kecamatan Paguyangan - Brilianti Ade Saputri (Institut Agama Islam Negeri Purwokerto, 2020)
It’s a case study research by using descriptive qualitative approach. Aimed to give the representation class management of planning, organizing, implementing, and evaluating on class management of the excellent class’ mathematics learning on MTs Nurul Huda NU Pesanggrahan, Kecamatan Paguyangan. The subjects of this research was the headmaster, mathematics teachers, and students. Interview and observation is used to collect the data by using triangulation processes and the analysis technique used inductive analysis from Miles and Huberman. The result of the mathematics study management as follow: 1). Planning phase by preparing materials, lesson plan, and learning media. 2). Organizing phase use scientific approach and by involving them to understand materials, solve the problems, relating the materials in daily life, and use IT. 3). Implementing phase begins by reviewing previous materials, exercises, and convey the main materials. 4). Evaluating by giving different exercises that aimed to develop the question correctly.